The Association between Family Knowledge and Response with Pre-hospital Delay among Stroke Patients: A Study from Rural Area of Cirebon, Indonesia - Ivanka, Muhammad Nabil Prawira; Pratiwi, Witri; Kusnandang, Agus (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Stroke is a non-communicable disease whose prevalence continues to increase in both young and old age groups. Stroke patients require immediate treatment at the hospital to prevent disability and death. Delayed treatment may result in a worse prognosis. Aims: To analyze the relationship between family knowledge and response with pre-hospital delay in stroke patients in Cirebon Regency, Indonesia. Methods: This cross-sectional study was conducted at Waled General Hospital, Cirebon Regency, Indonesia. The sampling technique used was consecutive sampling of patients hospitalized with stroke diagnosis from May 2024 to July 2024. Patients with recurrent stroke were excluded. Data were collected from medical records and questionnaires administered to the patient's families. The Indonesian version of Stroke Recognition Questionnaire (SQR) was used to explore family knowledge, while family responses were explored using the Stroke Action Test (STAT). Results: There were 61 stroke patients recruited in this study. Majority of the sample were delivered to hospital late (78.7%). Most of the patients’ families had poor knowledge (47.5%) and inadequate attitudes (85.2%). In the bivariate analysis, there was a strong correlation between family knowledge of stroke symptoms and pre-hospital delay (p=<0.001; r=0.746). Inadequate family response was associated with pre-hospital delay [p= 0.002; PR 2.596 (95%CI 1.024-6.581)]. Conclusion: There is a positive correlation between family knowledge and response with pre-hospital delay in stroke patients in Cirebon Regency, Indonesia. Received: 26 September 2024 | Reviewed: 19 October 2024 | Revised: 24 November 2024 | Accepted: 30 November 2024.